Renormalization of the one-pion-exchange interaction - Frederico, T.; Timóteo, V. S.; Tomio, Lauro [UNESP] (Elsevier, 1999)
A renormalization scheme for the nucleon-nucleon (NN) interaction based on a subtracted T-matrix equation is proposed and applied to the one-pion-exchange potential supplemented by contact interactions. The singlet and triplet scattering lengths are given to fix the renormalized strengths of the contact interactions. With only one scaling parameter (μ), the results show an overall very good agreement with neutron-proton data, particularly for the observables related to the triplet channel. The agreement is qualitative in the 1 S0 channel. Between the low-energy NN observables we have examined, the mixing parameter of the 3S1-3D1 states is the most sensitive to the scale. The scheme is renormalization group invariant for μ → ∞. © 1999 Elsevier Science B.V. All rights reserved.
Keywords: Few-body; N-N effective interactions; Non-relativistic scattering theory; Renormalization